Malformation in index pregnancy in women with epilepsy is not followed by recurrence in subsequent pregnancy. Issue 12 (18th October 2013) - Begum, Shehanaaz; Sarma, Sankara P.; Thomas, Sanjeev V.
Summary Use of antiepileptic drugs (AEDs) in pregnant women with epilepsy (WWE) is associated with an increased risk of major congenital malformations (MCM). Previous studies have suggested that WWE who had a malformation in their index pregnancy were at an increased risk of recurrence in future pregnancies. We aimed to assess the risk of recurrence of MCM in 1, 616 WWE from Kerala Registry of Epilepsy and Pregnancy. The pregnancy outcome of women (n = 246) with two prospective pregnancies in the registry were analyzed. They had partial seizures with or without generalization (57.3%) or generalized seizures (42.7%). Polytherapy was used in 26.4% (index pregnancy) and 23.6% (follow‐up pregnancy). The mean dosage of AED for valproate was 498 mg/day and carbamazepine was 555 mg/day. The malformation rate in the index pregnancy was 8.5% (21/246) and in the follow‐up pregnancy was 8.9% (22/246) with only one recurrence. There was no increased risk of MCM in follow‐up pregnancy for those who had MCM in the index pregnancy (p = 0.70; OR 0.49; 95% CI 0.06–3.80). The use of any specific drug, continuation of the same drug or a change in drug therapy between two pregnancies did not alter the recurrence risk.